Microstructures and dielectric relaxation behaviors of pure and tellurium doped CaCu3Ti4O12ceramics prepared via vibro-milling method - Worawut Makcharoen (2018)
In this work, we have reported microstructures and the dielectric properties of CaCu 3 Ti 4 O 12 (CCTO) ceramics doped with different proportions of TeO 2 dopant (mol%, x=0, 0.5%, 1.0%, 2.0%). The pure and tellurium doping CCTO ceramics were prepared by a conventional solid-state reaction method and the effects of TeO 2 doping on the electrical properties and microstructures of these ceramics were investigated. XRD analysis confirmed the formation of single-phase material in samples. Scanning electron microscopy (SEM) is used in the micro structural studies of the specimens, which showed that TeO 2 doping can reduce the mean grain size and increasing size of an abnormal grain growth. Lattice parameter increases slightly with tellurium doping in CCTO, the dielectric constant reached a value as high as 18,000 (at 1 kHz) at a tellurium-doping concentration of 2.0 mol% and showed temperature stability at high frequency. The loss tangent of Te-doped CCTO ceramics was less than 0.05 at 1 kHz region below 105 °C. The loss tangent properties could be interpreted by the internal barrier layer capacitor model and the impedance measurement data. © 2012 Elsevier Ltd and Techna Group S.r.l.